Keragaman Kultur sebagai sebuah kenyataan - Choirunnisa Tri Ana Harahap (Business Finence Analyst Co.,, 2023)
Every continent is occupied by multicultural societies that have positive potential for assimilation and social integration. However, there is also a great opportunity for social conflict. The cultural diversity of the world's population consists of various tribes, ethnicities, religions and races, which if these differences are not communicated and not socialized properly will cause conflicts such as discrimination and radicalism. Multicultural education is a value education that must be instilled in order to have a multiculturalistic view and attitude, so that it is accustomed to coexisting with the diversity of characters and cultures, religions and languages, respecting the rights of every citizen regardless and distinguishing ethnic majority or minority. The purpose of this study is to describe the main data about the reality of religious, ethnic and linguistic diversity on five continents. This type of research is qualitative research with a literature review method. The results show that there is a vulnerability to conflict in multicultural life and the most effective way is through multicultural education to encourage the positive potential of differences.